Functional and anatomical correlates of word-, sentence-, and discourse-level integration in sign language - Inubushi, Tomoo; Sakai, Kuniyoshi L. (Frontiers in Human Neuroscience, 2013)
In both vocal and sign languages, we can distinguish word-, sentence-, and discourse-level integration in terms of hierarchical processes, which integrate various elements into another higher level of constructs. In the present study, we used magnetic resonance imaging and voxel-based morphometry to test three language tasks in Japanese Sign Language (JSL): word-level (Word), sentence-level (Sent), and discourse-level (Disc) decision tasks. We analyzed cortical activity and gray matter volumes of Deaf signers, and clarified three major points. First, we found that the activated regions in the frontal language areas gradually expanded in the dorso-ventral axis, corresponding to a difference in linguistic units for the three tasks. Moreover, the activations in each region of the frontal language areas were incrementally modulated with the level of linguistic integration. These dual mechanisms of the frontal language areas may reflect a basic organization principle of hierarchically integrating linguistic information. Secondly, activations in the lateral premotor cortex and inferior frontal gyrus were left-lateralized. Direct comparisons among the language tasks exhibited more focal activation in these regions, suggesting their functional localization. Thirdly, we found significantly positive correlations between individual task performances and gray matter volumes in localized regions, even when the ages of acquisition of JSL and Japanese were factored out. More specifically, correlations with the performances of the Word and Sent tasks were found in the left precentral/postcentral gyrus and insula, respectively, while correlations with those of the Disc task were found in the left ventral inferior frontal gyrus and precuneus. The unification of functional and anatomical studies would thus be fruitful for understanding human language systems from the aspects of both universality and individuality.